One-Step Screening and Process Optimization Experiments. - Lawson, John (American Statistician, 2003)
The writer examines certain orthogonal array experiments and provides examples of one-step screening and optimization. He contends that one-step screening and optimization experiments are a feasible alternative to sequential experimentation limited by time or budget. He also suggests that some designs thought to be useful for only screening experiments can also be useful for detecting interactions, fitting quadratic models to a subset of the factors, and identifying optimal operating conditions within the ranges studied when they are combined with suitable methods of data analysis.